Adsorption Technique for Color Removal from Aqueous Solution using Nano NiO as Adsorbent - Sadiq Ali, Omar; Edan AL-Mammar, Dunya (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
In the present study, nickel oxide nanoparticles (NiO-NPs) were synthesized using the aqueous extract of two leaf plants, Allium porrum (Leek) NiO-P and Apium graveolens (Celery) NiO-G, as reducing agents. The synthesized NiO-NPs were utilized as adsorbents to remove Biebrich Scarlet (BS) dye from water using the adsorption technique. The NiO-P and NiO-G surfaces were characterized using Fourier transform infrared (FTIR), X-ray diffraction (XRD), atomic force microscopy (AFM), scanning electron microscopy (SEM), and Brunauer-Emmett-Teller (BET). The batch adsorption experiments were achieved to explore the optimum conditions for the adsorption of BS dye onto the synthesized NiO-NPs, such as NiO-NPs dosage, initial concentration of BS, contact time, temperature, and pH. The equilibrium data of BS adsorption on NiO-P and NiO-G surfaces best fitted the Langmuir isotherm model. Thermodynamic data such as ΔG°, ΔH°, and ΔS° were also estimated. The adsorption of BS dye onto NiO-P and NiO-G surfaces is a spontaneous and endothermic process. The adsorption rates were calculated by pseudo-first-order (PFO) and pseudo-second-order (PSO) kinetics models, and it was obtained that the correlation coefficient R2 for PSO was in the range of 0.9762-0.9971 and 0.9408-0.9966 for NiO-P and NiO-G, respectively. Furthermore, the qe cal values for PSO are almost in agreement with the experimental qe exp at all temperatures. As a result, the rate mechanism is well explained by the pseudo-second-order model (PSO).